IMPLEMENTASI KEBIJAKAN PENGELOLAAN PASAR INDUK (TERPADU) KOTA LHOKSEUMAWE - Nura Ustrina; Aiyub; Ferizaldi, Ferizaldi; Nur Hafni (Jurnal PubBis, 2024)
The current condition of the Integrated Central Market in Lhokseumawe City is highly concerning, with traders not occupying the market and parts of the building already damaged, despite the market being newly constructed under a multiyear scheme from the Lhokseumawe City regional budget starting in 2018. This study examines the management policies of the Integrated Central Market in Lhokseumawe City. The research method used is qualitative, with data sources obtained through observation, interviews, and documentation techniques. The data was analysed using descriptive analysis following the concept of Miles and Huberman with three steps of data analysis: data condensation, data display, and conclusion drawing/verification. The results of this study indicate that the management policies of the Integrated Central Market do not align with the initial planning design. The initial plan by the Lhokseumawe City government was to establish the building as a central market; however, it was later repurposed as a warehouse. The market management policies also fall short of the substance of the Minister of Trade's regulations concerning Guidelines and Development of Traditional Markets, Shopping Centres, and Modern Stores, and the absence of specific regional regulations has impeded the success of the policy. Issues such as policies deviating from the initial plans, the loss of resources and infrastructure, and a lack of communication between organisations and actors involved in carrying out their functions and duties have arisen due to an inadequate feasibility study. This has led to the market not being fully operational and being repurposed as a warehouse, when it should have been utilised for other, more productive activities that could contribute to the region, rather than becoming an abandoned or damaged building. Keywords: Implementation, Policy, Market Management